Numerical Study of the Vertical Hydrological Structure of the Black Sea Under January Atmospheric Climatological Forcing - Demetrashvili, Demuri I.; Kvaratskhelia, Diana U.; Kukhalashvili, Vepkhia. G. (Journals of Georgian Geophysical Society, 2017)
This paper is devoted to the analysis of the vertical structure of circulation and thermohaline fields in the Black Sea for January climatic conditions on the basis of a 3-D baroclinic model of the Black Sea dynamics with 5 km resolution. The model makes it possible to take into account wind driven forcing with alternation of different climatic wind fields and the atmospheric thermohaline action by both the Dirichlet conditions through setting the temperature and salinity at the sea surface and the Neumann conditions through setting the heat fluxes, evaporation, and atmospheric precipitation. The analysis of the performed numerical experiment has shown that within the layer with depth 0 - 300 m the sub-layers are forming with variable depth in time due to the simultaneously influence of the nonstationarity of atmospheric circulation and thermohaline processes. Within each sub-layer circulation characteristics practically do not change on a vertical but they undergoes some changes in time.